Cowpea seed treatment with carbosulfan: potential for control of seedling pests - Jackai, L.E.N.; Roberts, J.M.F.; Singh, S.R. (1988)
Results from three field trials and a screenhouse study conducted in 1985 and 1986 using carbosulfan (Marshal 25 ST) insecticide dust formulation at 0, 10, 20, 30 and 40 g/kg cowpea seed indicated that infestation and/or damage by aphids, foliage beetles and leafhoppers was satisfactorily reduced with treatment levels above 20 g carbosulfan/kg seed. The period of activity of the different treatments ranged from 15 to 23 days for various pests in the screenhouse, and slightly longer in field trials. Post-flowering pests were, however, not controlled at any of the rates tested. The ease of application and high dermal LD50 (> 2000 mg/kg rabbit) make Marshal 25 ST a very attractive option for use by small-scale farmers as a component of an integrated pest management strategy in locations where these pests are important and adequate levels of genetic resistance are not available.